Breaking the pendulum: the long struggle over criminal justice - Goodmann, Philip Russell (Oxford University Press, 2017)
Penal development and plate tectonics -- The pain of penitence: battling over criminal justice in early America -- Reform and repression in the progressive era -- Rehabilitation: all things to all people -- Deconstructing the carceral state -- Beyond the pendulum